A High‐Performance Microbial Battery Based on the Chemotactic Biofilm of a Motile Microaerophilic Bacterium. Issue 7 (20th May 2014) - Parthasarathy, Meera; Narayanan, Anantha; Narasimhan, Siddarth; Alex, Sruthi Ann; Ogirala, Vivek; Kalidasan, Viveka
Abstract Motile bacteria adapt themselves to changes in chemical environment by a stochastic mechanism called chemotaxis, which plays a major role in many bacterial processes. We report here for the first time that the preferential migration of bacteria across a nutrient gradient can be harnessed to generate useful electric power. The chemotactic battery demonstrated in the present work involves a nutrient‐localized anode toward which bacteria activated by starvation migrate and generate electricity by oxidation of the nutrient molecules. The chemotactic battery yields a significant power density (25±2 W m−2). Systematic investigation on biofilm morphology and electroactivity reveals significant differences between chemotactic and non‐chemotactic configurations. In addition, the chemotactic setup has also been integrated in the anode chamber of a microbial fuel cell to improve microbial biofilm properties. Thus the results of the study could be used to design miniature microbial batteries for portable applications as well as to improve the performance of microbial fuel cells.